Launching Effectiveness Research to Guide Practice in Neurosurgery: A National Institute Neurological Disorders and Stroke Workshop Report. Issue 4 (16th March 2017) - Walicke, Patricia; Abosch, Aviva; Asher, Anthony; Barker, Fred G.; Ghogawala, Zoher; Harbaugh, Robert; Jehi, Lara; Kestle, John; Koroshetz, Walter; Little, Roderick; Rubin, Donald; Valadka, Alex; et al.
Abstract: This workshop addressed challenges of clinical research in neurosurgery. Randomized controlled clinical trials (RCTs) have high internal validity, but often insufficiently generalize to real-world practice. Observational studies are inclusive but often lack sufficient rigor. The workshop considered possible solutions, such as (1) statistical methods for demonstrating causality using observational data; (2) characteristics required of a registry supporting effectiveness research; (3) trial designs combining advantages of observational studies and RCTs; and (4) equipoise, an identified challenge for RCTs. In the future, advances in information technology potentially could lead to creation of a massive database where clinical data from all neurosurgeons are integrated and analyzed, ending the separation of clinical research and practice and leading to a new "science of practice."